2017
DOI: 10.3390/nu9030209
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Share of Ultra-Processed Foods and Urinary Concentrations of Phytoestrogens in the US

Abstract: The aim of this study was to examine the relationship between dietary contribution of ultra-processed foods and urinary phytoestrogen concentrations in the US. Participants from cross-sectional 2009–2010 National Health and Nutrition Examination Survey aged 6+ years, selected to measure urinary phytoestrogens and with one 24-h dietary recall were evaluated (2692 participants). Food items were classified according to NOVA (a name, not an acronym), a four-group food classification based on the extent and purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 55 publications
0
27
0
1
Order By: Relevance
“…Studies have consistently shown that as the intake of ultraprocessed food increases, overall quality of diets deteriorates and becomes more obesogenic (Moubarac et al 2016;Louzada et al 2017;. Diets based on these foods are energydense, high in free and added sugars, saturated and trans fats, and depleted in most micronutrients and other bioactive compounds, fibre, and protein (Moubarac et al 2016;Louzada et al 2017;Steele and Monteiro 2017). Consumption of ultra-processed foods have also been associated with diet-related chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have consistently shown that as the intake of ultraprocessed food increases, overall quality of diets deteriorates and becomes more obesogenic (Moubarac et al 2016;Louzada et al 2017;. Diets based on these foods are energydense, high in free and added sugars, saturated and trans fats, and depleted in most micronutrients and other bioactive compounds, fibre, and protein (Moubarac et al 2016;Louzada et al 2017;Steele and Monteiro 2017). Consumption of ultra-processed foods have also been associated with diet-related chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the mechanisms underpinning the link between UPFs and adverse health outcomes is still emerging. Proposed mechanisms include a poor nutritional profile (i.e., UPFs are vectors for added sugars, sodium and trans-fats) and displacement of MPFs in the diet [ 33 , 34 , 35 , 58 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ], higher glycaemic load and reduced gut–brain satiety signalling resulting from altered physical properties created by the processing of foods [ 115 , 116 , 117 , 118 ], carcinogens formed during high-temperature cooking (e.g., carbohydrate-rich foods with acrylamide) [ 119 , 120 ], and inflammatory responses linked with acellular nutrients and industrial food additives, gut microflora dysbiosis and increased intestinal permeability [ 98 , 121 , 122 ]. Certain properties of UPFs may promote overconsumption [ 123 ], including their often ubiquitous availability and convenience [ 124 , 125 , 126 ], palatability and quasi-addictiveness [ 127 , 128 ] and intensive marketing practices used to promote purchasing and consumption, especially among children and adolescents [ 129 , 130 , 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the framework of NHANES, authors reported a strong inverse association between consumption of ultra-processed food and urinary concentrations of phytoestrogens. 37 A longitudinal study of pregnant women in the United States suggested that the percentage of total calorie intake from ultra-processed food might be a useful predictor of gestational weight gain and neonatal body fat. 38 …”
Section: Discussionmentioning
confidence: 99%